2003
DOI: 10.1159/000073359
|View full text |Cite
|
Sign up to set email alerts
|

Ifosfamide in Non-Small Cell Lung Cancer

Abstract: In recent years the role of chemotherapy in advanced non-small cell lung cancer (NSCLC) has been well established. Ifosfamide is an old drug still considered an effective cytostatic agent in the treatment of NSCLC. As a single agent, it has showed a response rate of 20–25%. These results are improved when it is used in combination with cisplatin and mitomycin C. Moreover, in recent years, several new drugs like gemcitabine, taxanes and vinorelbine have been identified, and combinations of two or three drugs ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…As a single agent, it has showed a response rate of 20-25% [21]. These results are improved when it is used in combination with cisplatin and mitomycin C [22]. The MIP regimen (mitomycin, ifosfamide, cisplatin) has showed better survival and quality of life compared to no chemotherapy, in big randomized multicenter trial with more than 800 patients [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a single agent, it has showed a response rate of 20-25% [21]. These results are improved when it is used in combination with cisplatin and mitomycin C [22]. The MIP regimen (mitomycin, ifosfamide, cisplatin) has showed better survival and quality of life compared to no chemotherapy, in big randomized multicenter trial with more than 800 patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…The MIP regimen (mitomycin, ifosfamide, cisplatin) has showed better survival and quality of life compared to no chemotherapy, in big randomized multicenter trial with more than 800 patients [23]. Recent trials showed equal response rates and survival by using MIP or GP (gemcitabine, platinum) regimen [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be pointed out that the dose of ifosfamide recommended in the phase II part of the above study was 1.5 g/m 2 /day over days 1 + 2 [43]. An overview of recent results obtained using ifosfamide in combinations with other newer active agents in advanced NSCLC (usually three-drug regimens) indicated that the addition of ifosfamide demonstrates an improvement in RR at the 50% level with a median survival of more than 1 year [44]. …”
Section: Discussionmentioning
confidence: 99%
“…5,7 With the co-administration of mesna uroprotection, the primary dose-limiting toxicity of ifosfamide is myelosuppression. 8 To improve the selectivity of tumor cell killing and the sparing of normal tissue, prodrug forms that can be selectively activated in tumor tissue have been widely investigated. There are several mechanisms potentially exploitable for selective prodrug activation in tumors including utilizing unique aspects of tumor physiology such as selective enzyme expression, hypoxia, and low extracellular pH.…”
Section: Introductionmentioning
confidence: 99%